ISRAEL AND AZERBAIJAN: TO COUNTERACT IRAN - KHALIFA-ZADEH, Mahir (CENTRAL ASIA AND THE CAUCASUS, 2012)
It is well known that Azerbaijan’s history does not have any anti-Semitic traditions. During the time of the Russian and Soviet empires, Azerbaijan was not poisoned by anti-Semitism. Obviously, anti-Semitism has not been an issue in Azerbaijan. Moreover, many famous Jews were born and studied in Azerbaijan. The brilliant scientist of modern physics and Nobel Prize Laureate Lev Landau was born in Baku, Azerbaijan, in 1908 and attended Baku State University in 1922.After the disintegration of the Soviet Union, the historically close and warm relations between the Jews and Azeris became a solid base for mutual cooperation between the State of Israel and the Republic of Azerbaijan. Both countries have a strategic location but an unfriendly foreign environment, which pushes them to be close and expand cooperation. Azerbaijan and Israel cooperate to counteract or neutralize foreign threats, which is the subject of this paper.